Let the two integers be x and y respectively
Hence;
![x + y = - 15 \\ \\ xy = 54](https://img.qammunity.org/2020/formulas/mathematics/high-school/org6cinzfxs8wtrz227e1sdis171g201ye.png)
From the first equation ;
![x = - 15- y](https://img.qammunity.org/2020/formulas/mathematics/high-school/e9t75488d9dcemf0tz2umncsmsb6gaa7dp.png)
Substitute into the third equation
![( - 15 - y)y = 54](https://img.qammunity.org/2020/formulas/mathematics/high-school/e6635e0taulh4etaz817qv33oh6t3m6p6n.png)
Open up the bracket
![- 15y - {y}^(2) = 54](https://img.qammunity.org/2020/formulas/mathematics/high-school/y4hrsr4e574oz6j0ncr3j5e1m1l92bxo12.png)
Take everything to the right hand side of the equation and you'll have a quadratic equation
![0 = 54 + 15y + {y}^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1z0cifbfihif75q5pm4ri4tg9qmla3ri4i.png)
Solve the quadratic equation and you'll have two roots
![y= - 6 \: or \: y= -9](https://img.qammunity.org/2020/formulas/mathematics/high-school/u9hm87h0zv5un9dhj5ebcydtzjlgyrh9mn.png)
Substitute for each value of y in the first equation
Therefore:
![x + ( - 6) = - 15 \: \\ or \\ \: x + ( - 9) = - 15](https://img.qammunity.org/2020/formulas/mathematics/high-school/82gk6ic8d8v245nwppfidbh3zdetipi7b4.png)
![x - 6 = - 15 \\ or \\ x - 9 = - 15](https://img.qammunity.org/2020/formulas/mathematics/high-school/czmvy4nw3nok260ixbn4y5b43c1ydygguy.png)
![x = - 15 + 6 \\ or \\ x = - 15 + 9](https://img.qammunity.org/2020/formulas/mathematics/high-school/3ym7idzvhhbg0dbsm5lk0t2qdqwgo8h9qk.png)
![x = - 9 \: or \: x = - 6](https://img.qammunity.org/2020/formulas/mathematics/high-school/e38yl6e2tt40tjqfz60gl6g8rpbpitpjw9.png)
Therefore the answer is A